Relation between age and fecundity of giant gouramy (Osphronemus gouramy) - Arif Habib Fasya; Hilda Nabila (Airlangga University, 2020)
The need for gouramy (Osphronemus gouramy) continues to increase, this can be seen from the gouramy trade which has begun at the egg stage, so research is needed that affects the number of eggs (fecundity) of the gouramy parent. In this study aims to determine the relationship between age and fecundity of gouramy. The research method used is comparative descriptive. Main gouramy fish is divided into 3 based on their age, pond A is 2.5 years old, pond B is 4 years old and pond C is 8 years old. Observations were made by taking eggs from the nest in each pond then counted manually. The observations showed that the parent who was 4 years old had the highest level of fecundity.Keyword : Age, Fecundity, Osphoronemus gourami